2016
DOI: 10.1007/s11095-016-2041-y
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Mechanisms of Polysorbate 20 Differentiated by 18O-labeling and Mass Spectrometry

Abstract: The O-labeling technique and unique degradant patterns of all-laurate PS20 described here provide a direct approach to differentiate the types of PS degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…This finding is consistent with a previous study, which showed that the degradation rate of di-and triesters of PEG sorbitan was much higher than that of monoesters in both PS80 and PS20. 14 Moreover, the relative abundance of non-esterified polyols seemed to be increased over time due to oxidative stress-induced ester scission 31 .…”
Section: Iron-induced Oxidative Degradation Of Ps80 Of Different Gradesmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with a previous study, which showed that the degradation rate of di-and triesters of PEG sorbitan was much higher than that of monoesters in both PS80 and PS20. 14 Moreover, the relative abundance of non-esterified polyols seemed to be increased over time due to oxidative stress-induced ester scission 31 .…”
Section: Iron-induced Oxidative Degradation Of Ps80 Of Different Gradesmentioning
confidence: 99%
“…1,2 A PS subspecies assay is an attractive tool in identifying the PS degradation pathways based on changes of subspecies profile and can be utilized as part of investigation when PS content decreases in protein samples. It provides an overview of PS subspecies (Figure 1) by separating each subspecies based on hydrophobicity, in combination with universal detectors such as mass spectrometer, [31][32][33][34][35] CAD, 13,36,37 and ELSD. 34 The advantage of using a mass spectrometer as a detector is that it is capable of identifying both PS subspecies and degradants based on accurate mass measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The stabilising properties of polysorbates in solution can be overshadowed by their susceptibility to autooxidation. The major sites for initiation of autooxidation for polysorbates include unesterified polyoxyethylenes [25], ester bonds [47] and the unsaturation sites of fatty acids [32,48]. Polysorbates are mixtures of various fatty acid esters.…”
Section: Polysorbates Degradation: Oxidation Of Polysorbates and Their Composition Profilesmentioning
confidence: 99%
“…Polysorbate materials are readily amenable to analysis by electrospray ionization (ESI; positive and negative) LC/MS as illustrated by the numerous recent publications, particularly from the biopharmaceutical industry, largely focusing on polysorbate stability. These range from more technique‐focused approaches, such as the use of radiolabeling and LC/MS and developing new multidimensional UHPLC/MS techniques to better characterize and monitor degradation in aqueous buffered formulations, through to the application of LC/MS to study degradation pathways. Such publications range from studies of potential degradation pathways for both Polysorbate 20 and Polysorbate 80 through to more specific investigations into the oxidative degradation of Polysorbate 80 and hydrolytic degradation of Polysorbate 20 and Polysorbate 80 .…”
Section: Results and Discussion By Techniquementioning
confidence: 99%